Ethics of scientific research and artificial intelligence: Importance and impact - Djamel, Griou (The International tax journal, 2025)
Researchers must possess distinctive qualities that qualify them to produce solid scientific research of cognitive value that contributes to serving society. No one can be considered a successful researcher unless they adhere to the values and standards upon which scientific research is based. Excellence is therefore measured by a researcher's commitment to research ethics and their strict adherence to them. This positively impacts the quality and academic standard of the research process, while simultaneously providing opportunities for excellence and competitiveness. This commitment also contributes to improving the quality of higher education outcomes by preparing qualified graduates capable of meeting the ever-evolving demands of the labor market.